Pengembangan Media Flipbook Digital Berbasis Kearifan Lokal untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Rini Febriani; Hairunisa Hairunisa; Syafruddin Syafruddin (Lembaga Bale Literasi, 2025)
This study aims to develop a digital flipbook media based on local wisdom that is valid, practical, and effective in enhancing students' critical thinking skills in IPAS learning for fourth-grade students at SDN Inpres Rasabou. The approach taken in this study is Research and Development, following the ADDIE framework that consists of the phases: Analysis, Design, Development, Implementation, and Evaluation.. The research subjects were fourth-grade students at SDN Inpres Rasabou. Data collection techniques used expert validation questionnaires, student and teacher response questionnaires, as well as pretest and posttest assessments. The results showed that the digital flipbook media based on local wisdom obtained a material expert validation score of 90% (very valid) and a media expert validation score of 93% (very valid). Student responses were 93.33% and teacher responses were 100% (very practical). The pretest and posttest results showed a significant improvement with a n N-Gain score of 0.686, classified as moderate approaching high. Thus, this media valid, practical, and affective to be used to enhance critical thinking skills among elementary school students.